2023
DOI: 10.1002/anie.202305776
|View full text |Cite
|
Sign up to set email alerts
|

Copper (I)‐BOX Catalyzed Asymmetric 3‐Component Reaction for the Synthesis of Trifluoromethylated Propargylic Ethers and Anilines**

Abstract: An asymmetric 3‐component reaction between EthynylBenziodoXoles (EBXs), 2,2,2‐trifluorodiazoethane and nucleophiles catalyzed by a CuI‐BOX (Bisoxazoline) catalyst is described. This protocol gives access to chiral trifluoromethylated propargyl ethers and anilines, which are valuable building blocks in synthetic and medicinal chemistry. The reaction proceeds with high enantioselectivity and yield with different nucleophiles such as primary, secondary and tertiary alcohols, as well as both electron‐rich and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Unfortunately, the system failed to furnish the target product 4a (Table , entry 1). Since copper catalysts are widely used in the activation of alkynes to form alkynyl copper intermediates as well as carbene-transfer reactions with alkynes, the reaction was subsequently examined using CuCl as a cocatalyst, and 4a was detected in a moderate yield (40%, entry 2). Upon exploring the Rh­(II) catalysts, it was found that the three-component coupling product 4a can be obtained in nearly quantitative yield in the presence of Rh 2 (TFA) 4 (1.0 mol %) and Xantphos (1.5 mol %) with CuCl (5.0 mol %) as the cocatalyst, and this combination was much better for the reactions than that of Rh 2 (OAc) 4 or Rh 2 (Oct) 4 (entry 4 vs 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the system failed to furnish the target product 4a (Table , entry 1). Since copper catalysts are widely used in the activation of alkynes to form alkynyl copper intermediates as well as carbene-transfer reactions with alkynes, the reaction was subsequently examined using CuCl as a cocatalyst, and 4a was detected in a moderate yield (40%, entry 2). Upon exploring the Rh­(II) catalysts, it was found that the three-component coupling product 4a can be obtained in nearly quantitative yield in the presence of Rh 2 (TFA) 4 (1.0 mol %) and Xantphos (1.5 mol %) with CuCl (5.0 mol %) as the cocatalyst, and this combination was much better for the reactions than that of Rh 2 (OAc) 4 or Rh 2 (Oct) 4 (entry 4 vs 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, some challenges and/or pitfalls can be conceived for the proposed transformation. For example, different transition-metal catalysts may react with diazo compounds to form metal-carbenoids that show distinct reactivities with two coupling partners, such as cyclopropenylation of alkynes [Scheme c­(i)], C–H insertion of alkynes/formation of allenes [Scheme c­(ii),(iii)], etc. Besides these reactions, direct C-allylation of terminal alkynes with allylic compounds as well as the dimerization or trimerization of terminal alkynes are further potential obstacles for reaction development.…”
Section: Introductionmentioning
confidence: 99%
“…3 Our group has used the EBx reagents in Cu-catalyzed multicomponent reactions with diazo compounds. 4 Furthermore, these reagents have been applied in gold catalysis by the groups of Hashmi and Liu for the alkynylation of enamines or the formation of unsymmetrical 1,3-diynes via a Cadiot–Chodkiewicz-type cross-coupling. 5 The metal-free oxidative alkynylation of carbonyl compounds was also described by Maruoka and co-workers.…”
mentioning
confidence: 99%